2020
DOI: 10.1177/1078155220934853
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of relapse patterns in patients with acute lymphoblastic leukemia treated with blinatumomab

Abstract: Introduction Blinatumomab is a CD19/CD3 bispecific T-cell engager (BiTE) antibody that simultaneously binds CD19 on the surface of B-cells and CD3 on the surface of T-cells, resulting in tumor cell lysis. It is approved for the treatment of patients with relapsed/refractory B-cell acute lymphoblastic leukemia (B-ALL) and in patients with minimal residual disease after intensive induction chemotherapy. Relapse patterns after treatment with blinatumomab have not been we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Blinatumomab is a bispecific antibody binding simultaneously to CD19 on the surface of B-cells and CD3 on the surface of T-cells leading to tumor cell lysis [ 12 ]. Compared to standard chemotherapy, Blinatumomab has shown promising results regarding long term survival in a randomized, multi-center trial [ 13 ] and is approved for the treatment of B-cell ALL [ 12 ]. Box warnings of Blinatumomab include neurological symptoms such as encephalopathy, convulsions, speech disorders, delirium, and balance disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Blinatumomab is a bispecific antibody binding simultaneously to CD19 on the surface of B-cells and CD3 on the surface of T-cells leading to tumor cell lysis [ 12 ]. Compared to standard chemotherapy, Blinatumomab has shown promising results regarding long term survival in a randomized, multi-center trial [ 13 ] and is approved for the treatment of B-cell ALL [ 12 ]. Box warnings of Blinatumomab include neurological symptoms such as encephalopathy, convulsions, speech disorders, delirium, and balance disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Sites of EMR included the CNS, kidney, lymph node, muscle, chest wall, and nasopharynx. In another recent study by Lau et al including adult patients with R/R B-ALL or with minimal residual disease positive and treated with blinatumomab, the EMR rate was 20% and included lymph nodes, pancreas, adrenal gland, kidneys, liver, left parotid gland, and brain [ 12 ]. In our case, the patient presented multiple EMR sites.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most patients still relapse eventually after primary response to blinatumomab therapy. These relapses are currently being extensively investigated and the data have thus far indicated that relapses are frequently found at immune-privileged extramedullary locations and some relapses have lost CD19 antigen expression, but more research is required to further elucidate these resistance mechanisms [ 18 , 19 ].…”
Section: Main Textmentioning
confidence: 99%